The mind managers - Schiller, Herbert I (Beacon Press, 1975)
Contents: Manipulation and the Packaged consciciousness; The knowledge industry the governmental component; The knowledge industry the military-corporate; Recreation and entertainment reinforcement for the stastus quo; The polling industry the measurement and manufacture of opinion...